Application of predicate logic for failure detection in SCADA systems - Alekseyev, M.; Udovyk, I.; Syrotkina, O. (Штучний інтелект, 2017)
We consider the task of failure detection and localization. It is based on the analysis of the information flow state change in the system. We suggest a structural and logical model to describe SCADA of any topology. It is possible to form diagnostic features of independent failure detection. They are based on the characteristic functions of three-valued logic. We determine the predicate system of knowledge representation to implement the method of SCADA diagnostics in the event of incomplete data.